EVALUATION OF PERIARTICULAR TISSUES BY ULTRASONOGRAPHY IN PATIENTS WITH KNEE PAIN - Meltem Sayın,; Nehir Samancı,; Altan Kesici,; Tiraje Tuncer, (Archives of Rheumatology, 2001)
The purpose of this study was to investigate the periarticular lesions in patients who were admitted to our outpatient clinic with the complaint of knee pain. Ninety-one patients ( 17 male, 74 female) with no known metabolic or inflammatory articular disease were included in the study. All patients were undergone physical examination and knee ultrasonography (US). Mean age of the patients was 51,3 ± 14,1. US revealed 25% of the patients as normal. The patients had tendinitis (17.5%), Baker's cysts (16.4%), synovial hypertrophy (15,3%), bursitis(15,3%), synovial effusion (14,2%), and (13%) other findings such as synovial impingement, vascular changes, soft tissue mass. In addition, soft tissue lesions were detected by US in 11 (78%) of the 14 patients with the clinical and radiological diagnosis of knee osteoarthritis. In conclusion, assessment of periarticular tissues is useful for the diagnosis and treatment of patients with the complaint of knee pain. US, which is a nanivasive and inexpensive diagnostic method can be chosen for this purpose.